KUALITAS ORIENTED STRAND BOARD (OSB) DARI BAMBU HAUR HIJAU (Bambusa vulgaris) DAN KAYU KARET (Hevea brasiliensis) BERDASARKAN SUHU DAN WAKTU KEMPA - Suhadi, .; Indrayani, Yuliati; Yani, Ahmad (Universitas Tanjungpura, 2018)
This study aims at determining the effect of temperature and pressing time on the physical and mechanical properties of Oriented Strand Board (OSB) from the mixture of haur hijau bamboo and rubber wood and to get information related to temperature treatment and pressing time resulting the best physical and mechanical properties of OSB. The board size was 30 cm x 30 cm x 1 cm with target density of 0.75 g / cm3. The type of adhesive used is phenol formaldehyde. The face and back layers use a rubber wood strand while the core layer use a strand of haur hijau bamboo with a ratio of 1: 1: 1. The method used is a factorial experiment in random design complete (RAL) which consists of two factors. Factor A is the pressing temperature comprising 1600C and 1700C, while the B factor is the duration of the pressing time consisting of 7 minutes, 10 minutes and 12 minutes. The pressures used in the study is Â± 25 kg / cm2 and the adhesive concentration is 10%. The testing of physical and mechanical properties accordance with JIS A 5908-2003 standard. The results of the research showed that all temperature and all pressing time treatment produced the OSB that meets the JIS Standard 5908-2003 (Base Particleboard Type 24-10). The best quality OSB is noted at the 1700C of pressing temperatures and 10 minutes of pressing time.Keywords : haur hijau bamboo, oriented strand board (OSB), physical and mechanical properties, rubber wood, temperature and pressing time